1983
DOI: 10.1021/jo00156a018
|View full text |Cite
|
Sign up to set email alerts
|

Crown cation complex effects. 22. Enhancement of cation binding in lariat ethers bearing a methyl group at the quaternary, pivot carbon atom

Abstract: A number of carbon-pivot lariat ethers have been prepared and compared, with their counterparts having a methyl group bonded to the side-arm-bearing or pivot carbon. All of the compounds examined are 15-crown-5 derivatives, and in this series, the methyl lariats invariably show a higher affinity for sodium than do the nonmethylated species. The results are less consistent in the case of potassium cation which is larger than the 15-crown-5 compound's cation binding hole. The enhanced stability constant observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

1983
1983
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 7 publications
1
26
0
1
Order By: Relevance
“…T. Kikui et al have also previously reported that a family of monoazacrown ethers containing two hydroxy groups can be obtained by reaction of glycidyl ethers with primary amines and ammonia in water and methanol [18]. It is important to emphasize that reactive crown ethers are potentially important key intermediate compounds for highly functionalized derivatives such as crown polymers [19,20], bis(crown-ethers) [21,22], lariat ethers [23][24][25], and synthetic ionophores [26,27]. Nakatsuji et al described the synthesis of novel crown ethers having two bromomethyl groups which showed that reactive groups in the crown ring provide new reactive macrocycles with new properties and therefore, they have new possible applications [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…T. Kikui et al have also previously reported that a family of monoazacrown ethers containing two hydroxy groups can be obtained by reaction of glycidyl ethers with primary amines and ammonia in water and methanol [18]. It is important to emphasize that reactive crown ethers are potentially important key intermediate compounds for highly functionalized derivatives such as crown polymers [19,20], bis(crown-ethers) [21,22], lariat ethers [23][24][25], and synthetic ionophores [26,27]. Nakatsuji et al described the synthesis of novel crown ethers having two bromomethyl groups which showed that reactive groups in the crown ring provide new reactive macrocycles with new properties and therefore, they have new possible applications [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of phenolic precursors, the conversion to the glycidyl ether could be accomplished in a single step. Hydrolysis with dilute perchloric acid afforded the corresponding diol 9 , as illustrated in Scheme [25].…”
Section: General and Specific Synthesis Of C‐pivot Lariat Ethersmentioning
confidence: 99%
“…At first, we attributed this finding to "sidedness", that is, the sidearm must always be over the same face of the macroring. In collaboration with Okahara (11,12), we prepared a number of macrocycles having a geminal methyl group at the pivot atom. The binding strengths for these quaternary-methyl lariats were substantially higher than when the methyl group was absent.…”
Section: Single-armed Carbon-pivot Lariat Ethersmentioning
confidence: 99%